Global Research Trends on Human-Elephant Conflicts and Sustainable Plantation Management: A 30-Year Bibliometric Study - Priyambodo Priyambodo; Elly Lestari Rustiati; Dicky Dwi Alfandy; Siti Hamidatul ‘Aliyah; Nindy Permatasari (Journal of Bioresources and Environmental Sciences, 2026)
This study visualizes worldwide study patterns on human-elephant conflicts (HEC) and sustainable cultivation management across the last three decades using a thorough bibliometric assessment. The analysis, which uses VOSviewer to combine descriptive statistics, network visualization, and content-based clustering, is based on 342 Scopus-indexed documents published between 1995 and 2025. The results show a significant increase in research output following 2015, underscoring the growing interest in conserving biodiversity in plantation-driven landscapes within scientists and policymakers. Four main thematic clusters were found through co-citation and keyword analyses: policies supporting sustainable land management, community-based conservation and collaborative governance models, conflict mitigation and crop protection strategies, and ecological investigations on elephant behavior and habitat use. The findings point to a paradigm shift toward data-driven, interdisciplinary approaches that include climate adaptation tools, machine learning-based conflict prediction, and remote sensing. This research provides a fresh viewpoint and lays a solid basis for cooperative solutions combining ecological, technological, and socioeconomic aspects by connecting HEC studies with environmentally friendly plantation practices. To promote human-elephant coexistence while maintaining plantation output, future research should fill geographic understanding gaps, enhance cross-border collaborations, and broaden predictive analytics, especially in Southeast Asia.